Spatial Analysis of Provincial Primary School Graduation Rates in Indonesia in 2023 - Jannah, Rauhun; Taufik, M (JUPE : Jurnal Pendidikan Mandala, 2024)
classrooms (X2) as independent variables. A total of 34 samples were used, collected as secondary data from various Indonesian provinces during 2023-2024, accessed from the official website of the Ministry of Education, Culture, Research, and Technology. The results indicate that X1 is not significant (p-value=0.103), while X2 is significant (p-value=0.001) for the number of primary school graduates, indicating the significant influence of X2. The research findings suggest that the variable of the number of certified teachers (X1) does not significantly affect the number of primary school graduates. Conversely, the variable representing good classroom conditions (X2) is proven to significantly influence the number of primary school graduates. The policy recommendation is for the government and related institutions to prioritize the improvement and enhancement of school infrastructure, including conducive learning facilities and environments